Effect of Latex Adhesive Variation on the Quality of Torrefied Palm Shell Bio-briquettes - saragih, putwi aufa; Lince Muis (Journal of Innovation Process and Environmental Technology, 2025)
This study examined the impact of latex adhesive variations on torrefied palm shell bio-briquette quality. Bio-briquettes were produced using palm shell waste with latex adhesive ratios of 9:91%, 13:87%, 16:84%, 20:80%, and 23:77%. The torrefaction process was conducted at 300°C for 30 minutes. The bio-briquette quality parameters analyzed included calorific value, moisture content, ash content, volatile matter, fixed carbon content, and burning rate according to SNI 01-6235-2000 standards. Results showed that the calorific values ranged from 6,076-6,895 cal/gr, exceeding the minimum SNI requirement of 5,000 cal/g. Ash content met standards at 3.15-3.74% (requirement ≤8%). However, moisture content (15.32-20.16%), volatile matter (26.05-30.85%), and fixed carbon (45.79-55.47%) did not meet SNI specifications. The burning rate tests yielded 2,892-3,120 seconds. The optimal bio-briquette quality was achieved at a 23:77% latex adhesive:palm kernel shell ratio, demonstrating the highest calorific value and longest burning time. This research indicates that latex-bonded palm shell bio-briquettes show promise as an alternative fuel source, though further optimization is needed to meet all quality standards.